Multiresolution Approximations and Wavelet Bases of Weighted Lp Spaces - Aimar, Hugo Alejandro (2003)
We study boundedness and convergence on Lp(ℝn, dμ) of the projection operators Pj given by MRA structures with non-necessarily compactly supported scaling function. As a consequence, we prove that if w is a locally integrable function such that w -1/p-1 (x)(1+|x|)-N is integrable for some N > 0, then the Muckenhoupt Ap condition is necessary and sufficient for the associated wavelet system to be an unconditional basis for the weighted space L p(ℝn, w(x) dx), 1 < p < ∞.